Performance Study of Polarization Beam Splitters Based on Horizontal Slot Waveguide Operating at 700nm Wavelength - Salih, Salwa; Tawfeeq, Shelan (Iraqi Journal of Laser, 2023)
Abstract: Polarization beam splitter (PBS) integrated waveguides are the key components in the receiver of quantum key distribution (QKD) systems. Their function is to analyze the polarization of polarized light and separate the transverse-electric (TE) and transverse-magnetic (TM) polarizations into different waveguides. In this paper, a performance study of polarization beam splitters based on horizontal slot waveguide has been investigated for a wavelength of . PBS based on horizontal slot waveguide structure shows a polarization extinction ratio for quasi-TE and quasi-TM modes larger than  with insertion loss below  and a bandwidth of . Also, the fabrication tolerance of the structure is analyzed.